HPGDS is a novel prognostic marker associated with lipid metabolism and aggressiveness in lung adenocarcinoma - Shao, Fengling; Mao, Huajie; Luo, Tengling; Li, Qijun; Xu, Lei; Xie, Yajun (Frontiers in Oncology, 2022)
Abstract Background: Lung Adenocarcinoma (LUAD) is the most common respiratory tumor worldwide with a poor prognosis. Lipid metabolism is extremely important for the occurrence and development of cancer. However, the role of genes involved in lipid metabolism in the development of LUAD remains unclear. Methods: Based on differentially expressed genes involved in lipid metabolism in LUAD samples from The Cancer Genome Atlas (TCGA), abnormal lipid metabolism pathways in LUAD were analyzed. The lasso penalized regression analysis was subsequently applied to the TCGA cohort (training set) to construct a risk score formula. The predictive ability of the risk score was validated in the Gene Expression Omnibus (GEO) dataset (validation set) using K-M survival curves and ROC curves. Finally, based on CRISPR gene editing technology, HPGDS was knocked out in lung cancer cell lines, the changes of lipid metabolism-related markers were detected by western bolt, and the changes of cell invasiveness were detected by transwell. This paper aims to identify the abnormal lipid metabolism pathway of LUAD, construct a novel prognostic model of LUAD, and discover novel biomarkers involved in lipid metabolism in LUAD. Results: Based on the differential genes between lung cancer tissue and normal tissue, we found that the arachidonic acid metabolism pathway is both abnormal lipid metabolism pathway in lung adenocarcinoma and lung squamous cell carcinoma. Subsequently, based on the sample information of TCGA and abnormally expressed lipid metabolism-related genes, a 9-gene prognostic risk score was successfully constructed and validated in the GEO dataset. Finally, knockdown of HPGDS appears to promote lipid synthesis and is more invasive than control cells. Conclusion: The genes involved in lipid metabolism are related to the occurrence and development of LUAD. HPGDS may be a therapeutic target of a potential lipid metabolism pathway in LUAD, and more research on the therapeutic target of lipid metabolism genes in LUAD should be conducted.